Social status, preferences for redistribution and optimal taxation: A survey - Andrea Gallice (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
The author reviews recent studies that investigate how social status concerns influence individual preferences for redistribution and impact the design of optimal tax policies. He focuses on two aspects: the relevant dimension over which relative concerns are defined and the different formalizations of the notion of social status that the authors provide.
Keywords: D31; D62; H21; H23; 330; social status; redistribution; externalities; optimal taxation